Penerapan Pembelajaran Missouri Mathematic Project Untuk Meningkatkan Kemandirian Belajar Matematika (PTK Bagi Siswa Kelas VII A Semester Genap SMP Muhammadiyah 6 Surakarta Tahun 2013/2014) - Yayuk, Yayuk, Prof. Dr. Sutama, M.Pd (2014)
This Research aims to describe the increased independence of learning math for class 7A Muhammadiyah Surakarta 6 Junior High School learning through Missouri Mathematic Project. This research uses research action class. Data source derived from the teachers and students. Using data collection techniques of observation, tests, notes field, and documentation. Data analysis was conducted using the techniques of plot. The validity of the data by triangulation of sources and methods. Results of the Research, the application learning of Mathematic Missouri Project can increase independence of learning math in class 7A Muhammadiyah Surakarta 6 Junior High School, that is a) the activities of students completing their own tasks and responsibilities of the initial conditions of 57,57%, the first cycle of 78,12% then the second cycle of 96,55%, b) the activity of the students tackle their own problems from initial conditions of 48,48%, the first cycle of 59,37% then the second cycle of 86,2%, c) the activity of the students believe the ability of oneself from the initial conditions of 42,42%, the first cycle of 65,62% then the second cycle of 82,75, d) self-organize student activity from initial conditions of 21,21%, the first cycle of 34,37% then the second cycle of 65,51%.